2011
DOI: 10.1097/aci.0b013e32834a9676
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of allergic conjunctivitis

Abstract: Little focus has been set on the impact of allergic conjunctivitis as comorbidity to asthma and rhinitis in atopic patients. Conjunctivitis symptoms are at least as severe as rhinitis symptoms in patients with 'hay fever' and some have even generated the term of conjunctivorhinitis stressing the ocular symptoms. Prevalence studies should be specifically addressed to ocular allergy symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 35 publications
9
99
0
9
Order By: Relevance
“…The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 66%
See 1 more Smart Citation
“…The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 66%
“…Moreover, in children, AR is often comorbid with chronic middle-ear effusions, sinusitis, adenoidal and tonsillar hypertrophy and acute and serious otitis media [9]. The co-existence of allergic conjunctivitis in patients with AR is widely recognized [13,14]. In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15].…”
mentioning
confidence: 53%
“…Several advancing, mechanistic theories are supported by preliminary empirical data from a number of studies [25][26][27][28][29][30][31][32][33][34][35][36]40]. Allergic inflammation of the respiratory tract (evidenced by allergic asthma attacks) and eyes are highly correlated with air pollution levels [62,63]. The pollution increases oxidative stress, thus impeding the antioxidant defenses of the eye and inducing a cycle of inflammation and irritation, which strengthens allergen response, leading to clinical allergic conjunctivitis [64].…”
Section: Ijomeh 2016;29(3)mentioning
confidence: 99%
“…12,15 Majority of the patients (74.1%) in this study belonged to the 18-25 years age group and only 25.8% of the patients were above the age of 25 years. This was consistent with the studies done by John et al, and Abokyi et al, where the mean age of allergic conjunctivitis patients was about 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data, ocular and medical history, concomitant medications, physical examination, clinical examination including recording of vital signs, ophthalmological examination (ocular sign and symptom score) and details of drug prescription were recorded in the study proforma at baseline visit (visit 1) and all subsequent follow-up visits. [10][11][12][13] Follow-up visits were done on day 8 (visit 2) and day 15 (visit 3) after administering the study drugs. A deviation of ±1 day for first follow-up and ±2 days for subsequent follow-up was accepted.…”
Section: Methodsmentioning
confidence: 99%